Perceived effects of accreditation on education quality and health-related job outcomes: scales validation and correlates in Lebanon - Deema Rahme; Daniele Saade; Hala Sacre; Chadia Haddad; Samah Tawil; Samar Merhi; Randa Aoun; Aline Hajj; Fouad Sakr; Jihan Safwan; Marwan Akel; Rony M. Zeenny; et al. (BMC Medical Education)
Abstract Background This study examines the impact of program accreditation on education quality and career outcomes among students and graduates of health-related disciplines in Lebanon. In the absence of a national accrediting body, many universities seek international accreditation. Additionally, the study validates four scales measuring factors influencing university choice and perceptions of accreditation. Methods A cross-sectional study was conducted between September and December 2023, enrolling 642 participants, including students and graduates from Lebanese health-related programs. Four validated scales included: Reasons for Choosing University Program (RCUP, 14 items), Perception of University Program Accreditation (PUPA, 12 items), Perceived Impact on Education Quality (PI-AQE, 27 items), and Perceived Impact on Career Outcomes (PI-ACO, 9 items). Principal component analysis with Promax rotation assessed construct validity. Bivariate analyses (t-tests and ANOVA) examined relationships between scales and participant characteristics. Multivariate analysis of covariance (MANCOVA) adjusted for sociodemographic and university-related factors, while multiple regression explored predictors of time to employment for graduates. Results Students from three universities reported significantly lower RCUP scores, indicating weaker motivations for their program choice. Clear communication of accreditation status correlated positively with RCUP (β = 1.097, p = 0.004). Pharmacy students scored higher on RCUP (β = 2.412, p = 0.002). Higher income levels (β = 1.829, p = 0.020) and awareness of accreditation (β = 2.348, p = 0.004) were linked to more favorable PUPA scores. Females (β = 4.981, p = 0.002) and high-income individuals (β = 3.777, p = 0.040) anticipated a stronger impact on PI-AQE. Graduates, particularly those with a PhD (β = 4.755, p = 0.042) or a Bachelor’s degree (β = 2.557, p = 0.003), expressed more positive PI-ACO perceptions. Conversely, uncertainty about accreditation was associated with lower PI-ACO scores (β = -3.019, p = 0.004). Notably, university accreditation status (β = -0.355, p = 0.011) and longer professional experience (β = -0.274, p = 0.010) were significantly linked to a shorter time to employment. Conclusion This study validates tools for assessing accreditation’s impact on Lebanese health education. Findings emphasize that accreditation status, program choice, and demographics significantly shape perceptions of education quality and career prospects. Effective communication about accreditation may enhance career readiness and suggest potential benefits for employment prospects. These findings emphasize the importance of accreditation as a strategic tool for advancing health education quality and optimizing career prospects in the healthcare sector.